Efficacy and safety of adjunctive cenobamate: Post-hoc analysis of study C017 in patients grouped by mechanism of action of concomitant antiseizure medications. (March 2022) - Brandt, Christian; Sánchez-Álvarez, Juan Carlos; Steinhoff, Bernhard J.; Milanov, Ivan; Serratosa, Jose M.
Highlights: Cenobamate is a new antiseizure medication (ASM) for uncontrolled focal seizures. Adjunctive cenobamate is effective with sodium channel blockers (SCBs) and non-sodium channel blockers (non-SCBs). Marked reductions in seizure frequency with cenobamate occurred in both SCB and non-SCB groups. Seizure freedom was greater (up to 40.0%) with cenobamate vs placebo in the non-SCB group. TEAEs were similar across groups; however, dizziness occurred more often in the SCB group. Abstract: Purpose: To assess how efficacy and safety outcomes were affected when cenobamate was co-administered with antiseizure medications (ASMs) that use either sodium channel blocker (SCB) or non-sodium channel blocker (non-SCB) mechanisms of action (MoAs) in patients with uncontrolled focal seizures. Methods: An exploratory post-hoc analysis of a randomized, double-blind, placebo-controlled clinical study (YKP3089C017) was conducted. Baseline concomitant ASMs were grouped as either those that employed an SCB or non-SCB MoA. Efficacy was examined by cenobamate dose (100 mg, 200 mg, and 400 mg/day) and concomitant ASM group using responder rates (≥50%, ≥75%, ≥90% seizure reduction; 100% seizure reduction/seizure freedom) during the maintenance phase and median percentage seizure reduction during the double-blind period. Treatment-emergent adverse events (TEAEs) were examined in the double-blind period. Results: When co-administered with SCBs or non-SCBs, significantly higher percentages of patients achieved ≥50%, ≥75%, and ≥90% responder rates with cenobamate 200 mg/day and/or 400 mg/day versus placebo. Additionally, significantly higher percentages of patients achieved seizure freedom with cenobamate 400 mg/day versus placebo (SCB group, 17.5% versus 1.2%; non-SCB group, 40.0% versus 0.0%). Patients receiving 200 mg/day and 400 mg/day and concomitant SCBs and all patients taking cenobamate combined with non-SCB concomitant ASMs had significantly greater median percentage reductions in focal seizure frequency versus placebo. TEAEs were similar across groups; however, dizziness was more frequently reported in the SCB group. Conclusion: Cenobamate is a highly effective new treatment option for patients with uncontrolled focal seizures when co-administered with SCB or non-SCB ASMs.